Bezrobocie i bieda jako społeczne koszty "wielkiej zmiany" = Unemployment and poverty as social costs of the "great change" - Kaźmierczak-Kałużna, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Contemporary Polish poverty in the majority of cases is new one, resulting from social and economic transformations, modernisation processes and the system change. It is mainly the poverty of job market "outcasts", capable of working yet redundant in the new conditions.
Keywords: bezrobocie; bieda; transformacja ustrojowa; przemiany gospodarcze